Adaptive micro learning using fragmented time to learn - Sun, Geng (Intelligent information systems, 2020)
"This compendium introduces an artificial intelligence-supported solution to realize adaptive micro learning over open education resource (OER). The advantages of cloud computing and big data are leveraged to promote the categorization and customization of OERs micro learning context. For a micro-learning service, OERs are tailored into fragmented pieces to be consumed within shorter time frames"--Publisher's website